Retroactivity and contemporary art - Staff, Craig G., 1971- ([London] : Bloomsbury Academic, 2017)
"Contemporary art is often preoccupied with time, or acts in which the past is recovered. Through specific case studies of artists who strategically work with historical moments, this book examines how art from the last two decades has sought to mobilize these particular histories, and to what effect, against the backdrop of Modernism. Drawing on the art theory of Rosalind Krauss and the philosophies of Paul Ricoeur, Gerhard Richter, and Pierre Nora, Retroactivity in the Work of Contemporary Art interprets those works that foreground some aspect of retroactivity -- whether re-enacting, commemorating, or re-imagining -- as key artistic strategies. This book is striking philosophical reflection on time within art and art within time, and an indispensable read for those attempting to understand the artistic significance of history, materiality, and memory."--Bloomsbury Publishing.
Includes bibliographical references and index.
Also issued in print.
Electronic reproduction.
Keywords: Art, Modern -- 21st century; Art -- Philosophy